ESTIMATES OF THE POSSIBILITY OF RAPID METHANE WARMING 55 MA AGO - Golitsyn G.S.; Ginzburg A.S. (My University, 2007)
Alternation of relatively warm and cold periods in the Earth is well known from geological, geochemical, and paleoclimatic data. There are many different causes of significant changes in the global temperature of the Earth’s surface: variations in the parameters of the orbit, changes in the location of continents and oceans, falling of large asteroids, mass volcano eruptions, and others. The last decade of the 20th century was marked by the beginning of discussions concerning another possible cause of long-term (in the scale of the history of human civilization) and rather fast (in the geological time scale) climatic variations. This is the so-called methane catastrophe: emission of a large amount of methane from gas hydrates concentrated in the Earth’s interior. In our work, we estimate the principal possibility of rapid (during a few thousand years) greenhouse warming at the Paleocene/Eocene boundary (55 Ma ago) owing to methane emission from gas hydrates.
Keywords: Cenozoic::Paleogene::Paleocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Палеоцен; Кайнозой::Палеоген::Эоцен